An alternative elongational method to study the effect of saliva on thickened fluids for dysphagia nutritional support. (July 2018) - Turcanu, Mihaela; Siegert, Nadja; Secouard, Sébastien; Brito-de la Fuente, Edmundo; Balan, Corneliu; Gallegos, Crispulo
Abstract: Powder thickeners are used to modify liquid consistency in dysphagia management. These thickeners may contain starches, gums or their mixtures. Since the salivary α-amylase enzyme favours starch hydrolysis, this might affect the overall rheology of thickened fluids. This study provides a first insight into the impact of salivary α-amylase on the elongational properties of different types of thickened fluids, differentiating between gum-based and starch-based fluids, when considering the axial force developed during uniaxial elongation. The experimental results obtained in this study showed a dramatic decrease in the axial force as a result of salivary α-amylase addition to a pudding-like starch-based thickened fluid, while no significant change was observed after addition to a pudding-like gum-based thickened fluid. Monitoring axial forces during the stretching phase of CaBER was found to be a quick alternative method to identify structural changes of pudding-like thickened fluids in the presence of saliva, for which the conventional CaBER experiments are technically limited. Highlights: The shear and elongational behaviours of starch-based and gum-based thickened fluids were studied. The axial force developed during uniaxial elongation of different thickened fluids was studied. The effect of salivary α-amylase on the axial force of two different thickened fluids was studied. Axial force of a starch-based thickened fluid was highly affected by the addition of saliva. Axial force of a gum-based thickened fluid was unaffected by the addition of saliva.